Estabilidad de los servidores públicos bajo la modalidad de contratos ocasionales - Medina Mazzini, Eduardo (2021)
In this work we will try to measure the situation of the public official in a job, through the revision of the same legal regulations in the Public Function, which gives form to occasional contracts, it is possible that there is a violation of constitutional law But, once the doctrine, the law, the law of contracts, the constitutional jurisprudence, will proceed in the realization of this work to try to determine whether or not it corresponds through the contracts to give stability to the workers who are hired under this modality. In the methodological framework we will find that this investigation will be framed in obtaining information from the public official, who feels his right to work has been violated, consequently the norms of public law do not protect his stability, for the simple fact of having been hired, contrary to constitutional law and international regulations, in which the right to work must be respected............